2020
DOI: 10.4314/bajopas.v12i1.49s
|View full text |Cite
|
Sign up to set email alerts
|

Central nervous system depressant activity of ethanol leaf extract of <I>Globimetula braunii</I> (Engler) (Loranthaceae) growing on <I>Terminalia catappa</I> L. (Combretaceae)

Abstract: This study was carried out to determine phytochemical constituents, median lethal dose (LD50) and central nervous system depressant activity of ethanol leaf extract of Globimetula braunii using laboratory animal models. The intraperitoneal median lethal dose (LD50) of ethanol leaf extract of Globimetula braunii was determined in mice according to the method described by Lorke, 1983. The CNS depressant activity of Globimetula braunii leaf extract was determined using diazepam induced sleep, hole board t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
4
3
0
Order By: Relevance
“…Triterpenes were found to be absent in only aqueous fraction (Table 2). As in our earlier study it was reported that ethanol leaf extract of Globimetula braunii contained saponins, flavonoids, tannins, steroids, triterpenes and glycosides [5]. Similarly in the present study ethyl acetate and n-butanol to contain all secondary metabolites that are present in the crude extract.…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations
“…Triterpenes were found to be absent in only aqueous fraction (Table 2). As in our earlier study it was reported that ethanol leaf extract of Globimetula braunii contained saponins, flavonoids, tannins, steroids, triterpenes and glycosides [5]. Similarly in the present study ethyl acetate and n-butanol to contain all secondary metabolites that are present in the crude extract.…”
Section: Resultssupporting
confidence: 83%
“…From the result obtained n-hexane fraction is relatively safer than the chloroform, ethyl acetate and nbutanol. Moreover, n-hexane fraction has a higher median lethal dose compared to ethanol extract of Globimetula braunii (2800 mg/kg) as reported in previous study [5]. However, there is no significant difference between the normal saline (10 ml/kg) and the two lower doses of the n-hexane fraction (500 and 250 mg/kg) (Figure 1).…”
Section: Resultssupporting
confidence: 67%
See 2 more Smart Citations
“…8 Similarly, the ethanol leaf extract of G. braunii (growing on Terminalia catappa) was reported to possess central nervous system depressant activity and the effect was found to be comparable to that of diazepam. 12 Hexane fraction of the ethanol leaf extract of G. braunii (growing on Terminalia catappa) was also found to have significant central nervous system depressant activity. 13 Furthermore, the aqueous extract of G. braunii was found to exhibit oxytocic activity on the uterine smooth muscle in a dose-dependent manner; however, the effect was less potent compared to standard oxytocin in an in vitro study.…”
Section: Scientific Studies On G Brauniimentioning
confidence: 99%